Pengaruh Media Permainan Karet Gelang Dalam Pembelajaran Matematika Terhadap Pemahaman Konsep Perkalian di Kelas II Sekolah Dasar (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to determine the effect of rubber band game media in mathematics learning on the understanding of multiplication concepts in grade II elementary school students. This study uses a quantitative method with a quasi-experimental plan. The population of this study was all grade II students of SD Negeri 10 Tanjung Lago totaling 54 students. The sample of this study was class II A as the experimental class and class II B as the control class. Data collection techniques used were observation, testing, and documentation. The results of this study showed an average posttest score of the experimental class of 86 and a posttest score of the control class of 79. Based on the calculation of the SPSS 22 t-test, the sig value (2-tailed) was obtained at 0.016 <0.05 and the calculated t value was 2.483> 2006. So it can be concluded that Ha is accepted and Ho is rejected, meaning that there is an effect of rubber band game media in children's learning on the understanding of multiplication concepts in grade II elementary school students.